Electrolyte for sodium ion battery, sodium ion battery

By adding specific organic polymers to the sodium ion battery electrolyte, the problem of the darkening of the electrolyte in high temperature environments is solved, the cycle stability and safety of the battery are improved, and the long-term stability and efficient performance of the electrolyte are achieved.

CN119153794BActive Publication Date: 2025-03-25TIANNENG BATTERY GROUP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411640835.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-25
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing sodium ion battery electrolyte is prone to darken in high temperature environments, resulting in changes in the quality of the electrolyte, affecting battery performance, and still needs to be improved in cycle stability and safety.

Method used

Specific organic polymers are used as additives to the electrolyte and synthesize them through materials such as oxychloride, para-hydroxybenzaldehyde and 2,2-bis(3-aminophenyl)hexafluoropropane to form Schiff base and crown ether groups, which enhances the stability and hydrophobicity of the electrolyte.

Benefits of technology

Effectively slows down the increase in color of the electrolyte, improves the cycle stability and safety of the battery, reduces the moisture content of the electrolyte, and prolongs the use time of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153794B_ABST
    Figure CN119153794B_ABST
Patent Text Reader

Abstract

The present invention provides an electrolyte for a sodium ion battery and a sodium ion battery, and relates to the technical field of sodium ion batteries. The electrolyte for a sodium ion battery provided by the present invention comprises a sodium salt, an ester organic solvent and an additive. Among them, the additive comprises a phosphite group, a bistrifluoromethyl group and a crown ether group. The phosphite group provides electronic stability, enhances intramolecular interactions, and helps to improve the overall stability of the electrolyte; the bistrifluoromethyl group increases the hydrophobicity of the polymer, reduces the water content in the electrolyte, and improves the cycle stability and safety of the battery; the unique coordination ability of the crown ether group can adjust the solubility and mobility of metal ions and optimize the electrochemical properties of the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an electrolyte for a sodium ion battery and a sodium ion battery. Background Art

[0002] In recent years, emerging industries that use electrochemical energy storage as renewable energy have been developing rapidly. Among them, lithium-ion batteries (LIBs) have been widely used in power vehicles, 3C digital products, energy storage and other fields due to their high energy density, good cycle performance, high operating voltage and long service life. However, due to the limited lithium resources in my country, the price of lithium carbonate, the core raw material of batteries, has soared, and the cost of the entire battery manufacturing industry has surged.

[0003] Sodium-ion batteries (SIBs), as a new type of secondary battery, have the advantages of abundant sodium resources, excellent high and low temperature performance, and lower cost compared to lithium-ion batteries. Therefore, the research and development of sodium-ion batteries has received widespread attention.

[0004] In sodium-ion batteries, the positive electrode material and the negative electrode material, as important components, determine the overall performance indicators of the battery. As the intermediate bridge between the two, the electrolyte is an extremely important link in the transmission of sodium ions. Adding a small amount of functional molecules to the electrolyte can significantly improve the overall performance of the battery. However, the current exploration of sodium-ion batteries is mostly focused on the development of electrode materials and the improvement of performance, and there are relatively few reports on electrolytes.

[0005] Currently, most commercial sodium-ion battery electrolytes use sodium hexafluorophosphate (NaPF6) as the sodium salt. NaPF6 can be decomposed into phosphorus pentafluoride PF5, and PF5 causes the polymerization of ethylene carbonate, dimethyl carbonate or proton solvent impurities in the electrolyte to generate soluble monomers, dimers and oligomers.

[0006] For example, the invention application with publication number CN117577942A discloses an electrolyte for a sodium ion battery, a sodium ion battery and an electronic device. By selecting a conductive sodium salt to inhibit the side reactions of the electrolyte and improve the thermal stability of the electrolyte, the cycle stability, high and low temperature performance and safety performance of the sodium ion battery are effectively improved.

[0007] With the increase of conjugated systems in the polymer, the polymer spectrum red-shifts to reveal color-forming groups, resulting in an increase in the chromaticity of the electrolyte. Generally, the color of sodium-ion battery electrolytes will darken after being stored at 50°C for 24 hours, causing changes in the quality of the electrolyte, thereby affecting the performance of various sodium-ion battery properties.

[0008] The invention application with publication number CN117895081A discloses adding phosphite amine compounds as additives to non-aqueous electrolytes. The phosphite amine compounds include an amine group and a phosphite group. The phosphite group, as a Lewis base, can effectively capture the strong Lewis acid phosphorus pentafluoride. The trivalent phosphorus has a strong reducing property to prevent the amine from being oxidized, thereby inhibiting the increase in chromaticity during the storage of the electrolyte. However, there is still room for improvement in the cycle stability and safety of the battery.

[0009] Although the existing technologies have improved the cycle stability, electrochemical performance and safety performance of sodium-ion batteries to a certain extent, there are still many difficulties in achieving commercial application in terms of electrolyte color control, cycle stability and safety. Therefore, the development of a sodium-ion battery electrolyte with excellent performance has important application prospects. Summary of the invention

[0010] In view of the above-mentioned technical problems existing in the prior art, the present invention provides an electrolyte for a sodium ion battery and a sodium ion battery, and prepares a specific organic polymer as an additive for the sodium ion battery electrolyte, which further improves the cycle stability and safety of the battery while slowing down the increase in the chromaticity of the electrolyte.

[0011] In order to achieve the above object, according to one aspect of the present invention, an electrolyte for a sodium ion battery is provided, the electrolyte comprising a sodium salt, an ester organic solvent and an additive. The additive is an organic polymer, and the preparation method thereof comprises the following steps:

[0012] (1) In an inert atmosphere and with tetrabutylammonium bromide as a phase transfer catalyst, phosphorus oxychloride reacts with p-hydroxybenzaldehyde to obtain an aldehyde-containing phosphate derivative, which reacts with 2,2-bis(3-aminophenyl)hexafluoropropane (CAS No. 47250-53-3) to form a Schiff base, and then reacts with glacial acetic acid as a catalyst to obtain a polycondensation product;

[0013] (2) The polycondensation product is reacted with 4'-aminobenzo-18-crown-6 (CAS No.: 68941-06-0) to undergo a dehydration condensation reaction to obtain the organic polymer.

[0014] Preferably, the specific preparation method of the organic polymer is as follows:

[0015] T1: 1-10 parts by weight of phosphorus oxychloride, 50-70 parts by weight of toluene, 0.02-10 parts by weight of tetrabutylammonium bromide, 3-15 parts by weight of p-hydroxybenzaldehyde, 3-6 parts by weight of 2,2-bis(3-aminophenyl)hexafluoropropane and 0.01-2 parts by weight of glacial acetic acid are added to a sealed stirred reactor, nitrogen is introduced, and the reaction is stirred at 50-60° C. for 150-180 minutes;

[0016] T2: adding 0.03-0.6 parts of 4'-aminobenzo-18-crown-6, stirring and reacting at 50-60° C. for 100-150 minutes, and distilling off toluene to obtain the organic polymer.

[0017] Preferably, the mass of the organic polymer accounts for 0.01%-2% of the total mass of the electrolyte for the sodium ion battery. Further preferably, the mass of the organic polymer accounts for 0.5%-2% of the total mass of the electrolyte for the sodium ion battery. Within this mass percentage range, the growth of the electrolyte chromaticity and moisture is minimal. Even further preferably, the mass of the organic polymer accounts for 0.5%-1% of the total mass of the electrolyte for the sodium ion battery. Within this mass percentage range, not only the growth of the electrolyte chromaticity and moisture is minimal, but also the required cost is low. Most preferably, the mass of the organic polymer accounts for 0.5% of the total mass of the electrolyte for the sodium ion battery. Under this mass percentage, the growth of the electrolyte chromaticity and moisture is minimal, the battery's charge specific capacity and charge specific capacity retention rate are the highest, and the cost is the lowest.

[0018] Preferably, the sodium salt is selected from at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(oxalatoborate) (NaBOB), sodium tetrafluoroborate (NaBF4), sodium bis(fluorosulfonyl)imide (NaFSI) and sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), preferably sodium hexafluorophosphate.

[0019] Preferably, the concentration of sodium salt in the sodium ion battery electrolyte is 0.6-1.2 mol / L. The type and concentration of sodium salt used in the present application can be selected from the types and concentrations conventionally used in the prior art.

[0020] Preferably, the ester organic solvent is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC), preferably a mixed solution of dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate; further preferably, the mass ratio of dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate is (2-3.5): (2.1-4): (3-4). Most preferably, the mass ratio of dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate is 3:4:3. The type and concentration of the ester organic solvent in this application can be selected from the types and concentrations conventionally used in the prior art.

[0021] In order to achieve the above-mentioned object, according to another aspect of the present invention, a sodium ion battery is provided, comprising a positive electrode material, a separator, a negative electrode material and the electrolyte provided by the above-mentioned first aspect.

[0022] Preferably, the positive electrode material is sodium sheet, the negative electrode material is hard carbon, and the diaphragm is at least one of a polypropylene diaphragm, a polyethylene diaphragm, a composite diaphragm of polypropylene and polyethylene, an Al2O3 coated diaphragm, a glass fiber diaphragm, a polytetrafluoroethylene diaphragm, a cellulose diaphragm and an aramid diaphragm.

[0023] The present invention also provides a method for preparing the above electrolyte, comprising the following steps:

[0024] (1) In an argon glove box, one or more organic solvents are mixed and stirred to obtain a uniform mixed solution, and the solution is treated with molecular sieves for more than 48 hours to ensure that the water content is below 1 ppm;

[0025] (2) dissolving sodium salt in the mixed solution of step (1);

[0026] (3) Add the above additives to the mixed solution in step (2), and stir evenly at room temperature to obtain the electrolyte for sodium ion battery.

[0027] The beneficial effects of the present invention are as follows:

[0028] (1) The additive provided by the present invention has mild synthesis conditions and a relatively simple preparation method, and is suitable for large-scale industrial production;

[0029] (2) The additive provided by the present invention introduces a phosphite group (P(OC6H4CHO)3) through phosphorus oxychloride. The phosphite group provides electronic stability, enhances intramolecular interactions, and helps to improve the overall stability of the electrolyte;

[0030] (3) The additive provided by the present invention introduces a bistrifluoromethyl group (CF3) through 2,2-bis(3-aminophenyl)hexafluoropropane. The bistrifluoromethyl group increases the hydrophobicity of the polymer, reduces the moisture content in the electrolyte, and improves the cycle stability and safety of the battery;

[0031] (4) The additive provided by the present invention introduces a crown ether group through 4'-aminobenzo-18-crown-6, and its unique coordination ability can adjust the solubility and mobility of metal ions and optimize the electrochemical performance of the electrolyte;

[0032] (5) During the first charge and discharge process, the additive forms an SEI film containing -CH=N groups, which promotes the migration of sodium ions, reduces the consumption of sodium ions, reduces the irreversible capacity of the first charge and discharge, and improves the charge and discharge efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a graph showing the electrochemical test results of the electrolyte in Example 1 in the first week.

[0034] Figure 2This is a graph showing the electrochemical test results of the electrolyte in Example 2 in the first week.

[0035] Figure 3 This is a graph showing the electrochemical test results of the electrolyte in Example 3 in the first week.

[0036] Figure 4 This is a graph showing the electrochemical test results of the electrolyte in Example 4 in the first week.

[0037] Figure 5 This is a graph showing the electrochemical test results of the electrolyte in Example 5 in the first week.

[0038] Figure 6 This is a graph showing the electrochemical test results of the electrolyte in Example 6 in the first week.

[0039] Figure 7 This is a graph showing the electrochemical test results of the electrolyte of Comparative Example 1 in the first week.

[0040] Figure 8 This is the electrochemical test result of the electrolyte of Comparative Example 2 in the first week.

[0041] Fig. 9 This is the electrochemical test result of the electrolyte of comparative example 3 in the first week.

[0042] Fig.10 This is a graph showing the electrochemical test results of the electrolyte of Comparative Example 4 in the first week. DETAILED DESCRIPTION

[0043] Example 1

[0044] An organic polymer additive for sodium ion battery electrolyte, the preparation method of which comprises the following steps:

[0045] T1: 2 g of phosphorus oxychloride, 60 g of toluene, 0.02 g of tetrabutylammonium bromide, 4 g of p-hydroxybenzaldehyde, 3 g of 2,2-bis(3-aminophenyl)hexafluoropropane and 0.01 g of glacial acetic acid were added to a sealed stirred reactor, nitrogen was introduced, and the reaction was stirred at 50°C for 150 minutes;

[0046] T2: 0.4 g of 4'-aminobenzo-18-crown-6 was added, and the mixture was stirred and reacted at 60°C for 150 minutes. Toluene was distilled off to obtain an organic polymer, which was recorded as A1.

[0047] In a glove box filled with argon, dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate were mixed uniformly in a mass percentage of 3:4:3 to obtain an ester organic solvent. 100 g of the ester organic solvent was added with 14.8 g of sodium hexafluorophosphate to make a basic electrolyte with a concentration of 1.0 mol / L, and the electrolyte was recorded as B0. A1 accounting for 0.5% of the total mass of the electrolyte was then added, that is, 0.5 g of A1 was added to the basic electrolyte, and the electrolyte was recorded as B1.

[0048] Example 2

[0049] In this embodiment, the difference from Example 1 is that the mass of the electrolyte additive accounts for 0.01% of the mass of the electrolyte solvent, that is, 0.01 g of A1 is added to the basic electrolyte, and the electrolyte is recorded as B2.

[0050] Example 3

[0051] In this embodiment, the difference from Example 1 is that the mass of the electrolyte additive accounts for 0.1% of the mass of the electrolyte solvent, that is, 0.1 g of A1 is added to the basic electrolyte, and the electrolyte is recorded as B3.

[0052] Example 4

[0053] In this embodiment, the difference from Example 1 is that the mass of the electrolyte additive accounts for 0.2% of the mass of the electrolyte solvent, that is, 0.2g of A1 is added to the basic electrolyte, and the electrolyte is recorded as B4.

[0054] Example 5

[0055] In this embodiment, the difference from Example 1 is that the mass of the electrolyte additive accounts for 1% of the mass of the electrolyte solvent, that is, 1 g of A1 is added to the basic electrolyte, and the electrolyte is recorded as B5.

[0056] Example 6

[0057] In this embodiment, the difference from Example 1 is that the mass of the electrolyte additive accounts for 2% of the mass of the electrolyte solvent, that is, 2g of A1 is added to the basic electrolyte, and the electrolyte is recorded as B6.

[0058] Example 7

[0059] An organic polymer additive for sodium ion battery electrolyte, the preparation method of which comprises the following steps:

[0060] T1: 1 g of phosphorus oxychloride, 50 g of toluene solution, 0.02 g of tetrabutylammonium bromide, 3 g of p-hydroxybenzaldehyde, 3 g of 2,2-bis(3-aminophenyl)hexafluoropropane and 0.01 g of glacial acetic acid were added to a sealed stirred reactor, nitrogen was introduced, and the reaction was stirred at 50°C for 180 minutes;

[0061] T2: 0.03 g of 4'-aminobenzo-18-crown-6 was added, and the mixture was stirred and reacted at 60°C for 150 minutes. Toluene was distilled off to obtain an organic polymer, which was recorded as A2.

[0062] In a glove box filled with argon, dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate were mixed uniformly in a mass percentage of 3:4:3 to obtain an ester organic solvent. 100 g of the ester organic solvent was added with 14.8 g of sodium hexafluorophosphate to make a basic electrolyte with a concentration of 1.0 mol / L, which was recorded as B0. A2 accounting for 0.5% of the total mass of the electrolyte was then added, i.e. 0.5 g of A2 was added to the basic electrolyte, and the electrolyte was recorded as C1.

[0063] Example 8

[0064] An organic polymer additive for sodium ion battery electrolyte, the preparation method of which comprises the following steps:

[0065] T1: 10 g of phosphorus oxychloride, 70 g of toluene, 10 g of tetrabutylammonium bromide, 15 g of p-hydroxybenzaldehyde, 6 g of 2,2-bis(3-aminophenyl)hexafluoropropane and 2 g of glacial acetic acid were added to a sealed stirred reactor, nitrogen was introduced, and the reaction was stirred at 60°C for 150 minutes;

[0066] T2: 0.6 g of 4'-aminobenzo-18-crown-6 was added, and the mixture was stirred and reacted at 50°C for 100 minutes. Toluene was distilled off to obtain an organic polymer, which was recorded as A3.

[0067] In a glove box filled with argon, dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate were mixed uniformly in a mass percentage of 3:4:3 to obtain an ester organic solvent. 100 g of the ester organic solvent was added with 20.16 g of sodium hexafluorophosphate to make a basic electrolyte with a concentration of 1.2 mol / L, and the electrolyte was recorded as B1. A3 accounting for 0.5% of the total mass of the electrolyte was then added, that is, 0.5 g of A3 was added to the basic electrolyte, and the electrolyte was recorded as C2.

[0068] Example 9

[0069] An organic polymer additive for sodium ion battery electrolyte, the preparation method of which comprises the following steps:

[0070] T1: 5 g of phosphorus oxychloride, 60 g of toluene, 5 g of tetrabutylammonium bromide, 6 g of p-hydroxybenzaldehyde, 6 g of 2,2-bis(3-aminophenyl)hexafluoropropane and 1 g of glacial acetic acid were added to a closed stirred reactor, nitrogen was introduced, and the reaction was stirred at 60°C for 150 minutes;

[0071] T2: 0.3 g of 4'-aminobenzo-18-crown-6 was added, and the mixture was stirred and reacted at 50°C for 100 minutes. Toluene was distilled off to obtain an organic polymer, which was recorded as A4.

[0072] In a glove box filled with argon, dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate were mixed uniformly in a mass percentage of 3:4:3 to obtain an ester organic solvent. 100 g of the ester organic solvent was added to 10.08 g of sodium hexafluorophosphate to make a basic electrolyte with a concentration of 0.6 mol / L, and the electrolyte was recorded as B2. A4 was then added to account for 0.5% of the total mass of the electrolyte, that is, 0.5 g of A4 was added to the basic electrolyte, and the electrolyte was recorded as C3.

[0073] Comparative Example 1

[0074] In this embodiment, the difference from Embodiment 1 is that the basic electrolyte of A1 is not added.

[0075] Comparative Example 2

[0076] In this embodiment, what is different from Example 1 is that A1 is replaced with a film-forming additive VC, and the mass ratio of the electrolyte additive to the electrolyte solvent is 0.5%, that is, 1.5 g of VC is added to the basic electrolyte.

[0077] Comparative Example 3

[0078] In this embodiment, what is different from Example 1 is that A1 is replaced with a film-forming additive PCS, and the mass ratio of the electrolyte additive to the electrolyte solvent is 0.5%, that is, 1.5 g of PCS is added to the basic electrolyte.

[0079] Comparative Example 4

[0080] In this embodiment, what is different from Example 1 is that A1 is replaced with a film-forming additive FEC, and the mass ratio of the electrolyte additive to the electrolyte solvent is 0.5%, that is, 1.5 g of FEC is added to the basic electrolyte.

[0081] Test Example 1

[0082] (1) Preparation of negative electrode

[0083] The negative electrode material (hard carbon), superfine carbon powder (Super-P), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 94:2:1.5:2.5, that is, the masses of the above substances are 2g, 0.04g, 0.02g and 0.05g respectively, and then an appropriate amount of deionized water is added, and the mixture is stirred under the action of a vacuum disperser and dispersed until it is stable and uniform to obtain a negative electrode slurry; after filtering the negative electrode slurry, it is evenly coated on an aluminum foil with a coating thickness of 150μm, and dried in a vacuum drying oven at 120°C for 12h to obtain a negative electrode sheet.

[0084] (2) Preparation of sodium ion batteries

[0085] A 2032 button cell was prepared in a glove box using a positive sodium sheet, a negative electrode sheet and a separator.

[0086] Color test and moisture detection:

[0087] The electrolyte samples for sodium ion batteries of Examples 1-9 and Comparative Examples 1-4 were stored in a constant temperature oven at 50°C for 24h and 48h, respectively, and the chromaticity changes of the electrolytes after storage and the moisture changes at room temperature for 0 days, 30 days and 60 days were detected, as shown in Table 1.

[0088] Table 1 Changes in chromaticity and water content of electrolytes of Examples 1-9 and Comparative Examples 1-4

[0089]

[0090] According to the results in Table 1, compared with Comparative Examples 1-4, in Examples 1-6 at a high temperature of 50°C, the stabilizing additive A1 has a great influence on the chromaticity and moisture content of the sodium ion battery electrolyte. Adding 0.1%-2% of A1 significantly stabilizes the chromaticity of the sodium ion electrolyte, can reduce the moisture content of the electrolyte, extend the service life of the electrolyte, and improve the safety of the sodium ion battery.

[0091] Normal temperature cycle test:

[0092] The sodium ion batteries of Examples 1-6 and Comparative Examples 1-4 were tested in the voltage range of 0-2 V, activated at 0.1 C for three weeks, and cycled at 1 C for 100 weeks. The charging capacity at 0.1 C in the first week and the charging capacity retention rate after 10 weeks of 1 C cycle were recorded. The results are shown in Tables 2 and Figure 1-Figure 10 shown.

[0093] The first-week coulomb efficiency is the charge capacity / discharge capacity corresponding to 0.1C, and its calculation formula is:

[0094] Charging capacity / discharging capacity×100%.

[0095] After 10 cycles of charge and discharge, the 10th cycle retention rate is calculated using the following formula:

[0096] The 10th cycle charge capacity / the first cycle charge capacity × 100%.

[0097] Table 2 Battery electrical performance test results of Examples 1-6 and Comparative Examples 1-4

[0098]

[0099] The addition amount of A1 in Examples 1-6 is 0.5%, 0.01%, 0.1%, 0.2%, 1% and 2% respectively. From the first week charging capacity of the battery, it can be seen that with the increase of the addition amount of A1, the charging capacity of the battery shows an upward trend. However, when the addition amount of A1 exceeds 0.5%, the charging capacity of the battery shows a downward trend, and the battery charging capacity retention rate is the highest when the addition amount of A1 is 0.5%. Among them, the first week charging capacity of the battery in Example 1 is 331mAh / g, and the coulomb efficiency is 94.57%. Figure 1 ,Experiments show that batteries using electrolytes containing A1 additives can achieve better charging specific capacity.

Claims

1. An electrolyte for a sodium ion battery, comprising a sodium salt, an ester organic solvent and an additive, characterized in that: The additive is an organic polymer, and the preparation method of the organic polymer comprises the following steps: (1) Under the conditions of an inert atmosphere and a phase transfer catalyst, phosphorus oxychloride and p-hydroxybenzaldehyde undergo a substitution reaction to obtain a first reactant, the first reactant undergoes a condensation reaction with 2,2-bis(3-aminophenyl)hexafluoropropane to obtain a second reactant, and the second reactant undergoes a Schiff base condensation reaction in the presence of a catalyst to obtain a polycondensation product; (2) The polycondensation product undergoes a dehydration condensation reaction with 4'-aminobenzo-18-crown-6 to obtain the organic polymer.

2. The sodium ion battery electrolyte according to claim 1, characterized in that The specific preparation method of the organic polymer is as follows: T1: 1-10 parts by weight of phosphorus oxychloride, 50-70 parts of toluene, 0.02-10 parts of tetrabutylammonium bromide as a phase transfer catalyst, 3-15 parts of p-hydroxybenzaldehyde, 3-6 parts of 2,2-bis(3-aminophenyl)hexafluoropropane and 0.01-2 parts of glacial acetic acid as a catalyst are added to a closed stirred reactor, nitrogen is introduced, and the reaction is stirred at 50-60° C. for 150-180 minutes; T2: adding 0.03-0.6 parts of 4'-aminobenzo-18-crown-6, stirring and reacting at 50-60° C. for 100-150 minutes, and distilling off toluene to obtain the organic polymer.

3. The sodium ion battery electrolyte according to claim 1, characterized in that The mass of the organic polymer accounts for 0.01%-2% of the total mass of the electrolyte for the sodium ion battery.

4. The electrolyte for sodium ion battery according to claim 3, characterized in that The mass of the organic polymer accounts for 0.5%-2% of the total mass of the electrolyte for the sodium ion battery.

5. The sodium ion battery electrolyte according to claim 4, characterized in that: The mass of the organic polymer accounts for 0.5%-1% of the total mass of the electrolyte for the sodium ion battery.

6. The electrolyte for sodium ion battery according to claim 1, characterized in that The sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium bis(oxalatoborate), sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethanesulfonyl)imide.

7. The electrolyte for sodium ion battery according to claim 1, characterized in that: In the sodium ion battery electrolyte, the concentration of the sodium salt is 0.6-1.2 mol / L.

8. The electrolyte for sodium ion battery according to claim 1, characterized in that The ester organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate and butylene carbonate.

9. A sodium ion battery comprising a positive electrode material, an electrolyte, a negative electrode material and a separator, characterized in that: The electrolyte is the electrolyte for a sodium ion battery according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Electrolyte of sodium ion battery, sodium ion battery and electronic equipment

    CN117577942A

  • Non-aqueous electrolyte solution and battery

    CN117895081A

  • Phosphate cross-linking agent and preparation method thereof, phosphate-based cross-linked gel polymer electrolyte and preparation method and application thereof

    CN111499663A

  • Preparation method of Schiff base catalyst and preparation method of polyglycolic acid

    CN117209741A